Recovery of anthocyanins from sweet cherry wastes: process modeling and optimization using response surface methodology - Pereira, Carla (2018)
Sweet cherries (P. avium L.) are widely consumed fruits appreciated for their sweet taste and appealing appearance. Their colour vary with the maturation stage, being an excellent indicator of the optimal harvest time. When ripen, these fruits acquire a dark red coloration that is mainly influenced by the anthocyanin concentration in the fruit peel and pulp [1]. These compounds are present in several natural matrices and their colour can vary from blue to violet and red depending on the surrounding medium conditions (pH, temperature, humidity, salinity, stress and storage conditions, etc.) [2]. Beyond bioactive properties, these compounds also possess a great coloring capacity, which justify their increasing exploitation for food industry application, especially for cherry wastes recovery, given the fact that bird bitten and fallen fruits are not suitable for sale nor consumption and represent a significant part of the production. Thus, the aim of the present work was to optimize the extraction of these compounds from sweet cherry wastes, by studying the conditions that maximize the maceration extraction yield. For that purpose, a response surface methodology was applied using five levels for each of the independent variables (time, temperature, and solvent concentration). The quantification of anthocyanins present in the extracts was performed by high performance liquid chromatography coupled to a diode array detector (HPLC-DAD). For the model application, the anthocyanin concentration and the extraction yield were used as responses. Through this extraction method, it was possible to obtain a yield of 1.86±0.41 mg/g of cherry dry weight, in the optimal conditions of: 63.0±3.2 min; 61.7±1.3ºC and 53.1±1.4% of ethanol. The obtained residue represented 87% of the total cherry dry weight and the anthocyanin content was of 3.05±0.41 mg/g of dry residue. The results obtained in this study demonstrate the potential application of sweet cherries as sources of anthocyanins.